To "re-hatch" public employees or not? An ethical analysis of the relaxation of restrictions on political activities in civil service - Bowman, James S.; West, Jonathan P. (2009)
This study examines the ethical content of legislation regulating the political activities of civil servants. The analysis is done using the "ethics triangle", a tool that en-compasses the interdependence of results-based character ethics. The discussion begins with the importance of the problem, followed by its evolution and current status. After describing the methodology, the central section investigates the values at stake. The conclusion provides a synthesis of the findings, explores the implications of the study, and attempts to answer the question posed in the title of the paper. - Reproduced.
Keywords: Civil service